Blockchain Based Secure Online Voting System - Gouthami, C; Vidyulatha, G; Bhavani, K; Akhila, G (International Journal of Computer Sciences and Engineering, 2021)
Large sections of society today do not trust their government or election transparency. The issue with the current EVM system is that it can be easily manipulated by power-hungry organizations. Blockchain is a disruptive technology of current era and promises to improve the overall resilience of e-voting systems. This project presents an effort to leverage benefits of blockchain such as cryptographic foundations and transparency to achieve an effective scheme for e-voting. The proposed scheme conforms to the fundamental requirements for e-voting schemes and achieves end-to-end verifiability. We can achieve this e-voting scheme along with its implementation using Multichain platform. This project presents an effort to leverage benefits of blockchain such as cryptographic foundations and transparency to achieve an effective scheme for e-voting. This requires minimum requirements needed by a voter is a smartphone or a computer with a webcam and an internet connection. This private key public key wallet for users can completely eliminate chances of double voting. This will also lead to minimum involvement of human engagement and we can rely on a trusted software architecture. More number of voters would be able to participate in elections.